Role of NGOs for Women Empowerment in Nepal - Acharya, Chiranjivi (Darul Yasin Al Sys, 2025)
The purpose of this paper is to examine the role of non-government organization in upgrading the socio-economic status of Nepalese women with special reference to Melamchi Municipality-1, Majhuwa, Sindhupalchowk. NGOs in Nepal play a crucial role in the empowerment of women by providing education, economic resources, legal support, and healthcare services. They also advocate for policy reforms and cultural change, addressing the many barriers that women face. While challenges remain, the ongoing efforts of these organizations are laying the groundwork for a more equitable society where women can fully realize their potential. As UN (1995), the women empowerment is the systematic process to make women aware of gender based acquire a greater voice, unequal power relationships in which to speak out against the inequality found in workplace, home and communities. Thus, women could involves taking control over their lives, gaining skills, setting their own agendas, solving their problems and developing their self-reliance etc. This article will be useful to researcher, teachers, students and other concerning individuals and agencies. However, quantitative research methods, descriptive and analytical research designed, deductive approach is applied.